Determinants of readiness to implement forensic patient-oriented research: a study of barriers and facilitators in a high-secure hospital - Evans, Cara; Deljavan, Sevil; Zimmermann, Kayla; Allen, Kristy; Moghimi, Elnaz; Canning, Christopher (Frontiers in Psychiatry, 2025)
IntroductionForensic mental health care is intended to promote recovery and reintegration, but is often experienced by patients as punitive and aversive. Forensic patients are rarely engaged in research to explore what matters most to them, and little guidance exists on how this engagement may be facilitated. In this paper, we explore perceived determinants of readiness to implement forensic patient-oriented research in a high-secure setting.MethodsFollowing a period of engagement with staff and patients in the high-secure setting, we conducted interviews with 30 staff members (including clinicians, researchers, and hospital leaders) and five patients. We analyzed interviews using a thematic analysis approach. Coding was initially informed by the Consolidated Framework for Implementation Research, and subsequent iterations of analysis extended beyond this framework to explore patterns of meaning encompassing multiple implementation domains.ResultsWe identified three themes in our data: “Navigating a climate of distrust, discrimination, and restricted autonomy”; “Hearing and interpreting patient voices”; and “Experiencing a slow shift in the tide.” The first two themes represent potential challenges, including distrust and stigma; inherent restrictions in forensic care, and perceptions that patient autonomy threatens staff safety; patient fears of repercussions; and barriers to valuing and understanding patient voices. The third theme describes the ongoing shift towards patient-centredness in this setting, and participants’ interest in proceeding with forensic patient-oriented research.DiscussionIncreased attention to relationship-building, trauma-informed principles, and epistemic injustice (i.e., unfair devaluing of knowledge) in high-secure settings can support the involvement of forensic patients in research.